COAL MINING OPERATIONS AND ITS IMPACT ON SECTORAL AND REGIONAL AREA: EVIDENCE OF EAST KALIMANTAN, INDONESIA - Hilmawan, Rian; Yudaruddin, Rizky; Wahyuni, Yuyun Sri (Journal of Indonesian Applied Economics, 2016)
Mining sector plays important roles for Indonesian economic performance, especially in East Kalimantan. This study investigates: (a) whether economic linkages of the mining sector related with other economic sectors in East Kalimantan, (b) who gets benefit from such mining activities; (c) how is the impact of mining sector for rural and urban households; and (d) what happens if coal mining, oil and gas productions are completely depleted. The quantitative analysis framework using Input-Output and Social Accounting Matrix Tables in period 2009-2010 has been implemented as main data set. The result shows that mining sector was underdeveloped sector in East Kalimantan, including Kutai Kartanegara district. Activities from mining sector tended to give benefit for the owners of capital, which is larger than that benefit for workers employed. Structural Path Analysis (SPA) shows that urban households gain the greatest advantages from the activities of this sector. The result also shows that the total output decreased by 65.12% when the mining, oil and gas dissapeared. A drastic reducing income after mining and oil and gas era will have an impact on the decline in the purchasing power in the region. However, the interesting finding of this research shows that the loss of mining and oil or gas sectors actually increases the strength of employment multiplier by 19%.Â